2011
DOI: 10.1123/pes.23.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Within- and Between-Day Variability of Objectively Measured Physical Activity in Preschoolers

Abstract: In this study, physical activity (PA) was objectively measured in 213 Belgian preschoolers (M(age) = 4.98, SD = .88 years) over 4 consecutive days including two weekend days. Within-day variability in PA showed a typical activity pattern during weekdays and weekend days. Weekdays clearly reflected a preschool attending day with more peaks and troughs than weekend days and after-school hours were characterized by a decrease in activity. Between-day variability in PA was identified in preschool girls above the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
49
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 0 publications
21
49
9
Order By: Relevance
“…Homecare hourly patterns of PA determined in the current study are similar to the findings of Verbestel et al [22], whereby, two increases in children's activity levels on homecare days (i.e., Finnish) were recorded between 10 a.m. and 11 a.m. and 3 p.m. and 6 p.m. Additionally, Australian children's PA intensity levels were higher during hours between 11 a.m. and 12 p.m. These minor activity peaks were recorded slightly later than on childcare days.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Homecare hourly patterns of PA determined in the current study are similar to the findings of Verbestel et al [22], whereby, two increases in children's activity levels on homecare days (i.e., Finnish) were recorded between 10 a.m. and 11 a.m. and 3 p.m. and 6 p.m. Additionally, Australian children's PA intensity levels were higher during hours between 11 a.m. and 12 p.m. These minor activity peaks were recorded slightly later than on childcare days.…”
Section: Discussionsupporting
confidence: 91%
“…During this peak however, children's MVPA levels were lower than during the childcare hours. Congruent with results of the study of Verbestel et al [22], the Australian data confirmed that after childcare hours were associated with reduced activity levels. Parents may assume that their child is getting enough PA during the childcare day, which could limit encouragement of the child to be physically active or to play outdoors after childcare hours.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations